Foraging behavior of insectivorous birds in agricultural landscapes (Zoological Records and Reviews, 2023)
Insectivorous birds provide important pest regulation services in agricultural landscapes by consuming crop pest insects,yet their foraging behaviour and habitat use in intensively managed farmland remains poorly quantified in South Asiancontexts. Understanding how insectivorous birds use different crop and non-crop microhabitats for foraging, howpesticide application affects their prey availability and foraging success, and which landscape features support thehighest insectivore foraging activity is essential for quantifying the economic value of avian pest control services anddesigning bird-friendly farm management recommendations. This study examines the foraging behaviour of 24insectivorous bird species across paddy rice, vegetable, and mixed horticulture farms in Andhra Pradesh and Karnataka,India, using standardised focal animal watches, prey delivery rate measurements, and sentinel prey caterpillarexperiments at 48 farm sites over two crop cycles (2021-2022). Insectivorous birds collectively consumed 28.4-48.4insect prey items per hour per hectare in paddy fields during the vegetative growth stage, declining by 42.4% in the weekfollowing insecticide application. Sentinel prey experiments confirmed avian pest removal rates of 18.4-38.4% per 24hours in low-pesticide fields. Prey delivery rates were highest in paddy fields with field margin vegetation and lowest inbare-margin high-pesticide fields. The estimated economic value of avian insect control services ranges from INR 4,200to 12,400 per ha per season across crop types.
Keywords: pesticide impact; ecosystem services; Karnataka; Andhra Pradesh; paddy; sentinel prey; agricultural landscapes; pest control; foraging behaviour; insectivorous birds